Cryptogenic Organizing Pneumonia - Root, Michael Z; Lee, Joyce S. (Seminars in Respiratory and Critical Care Medicine)
Cryptogenic organizing pneumonia (COP), formerly called bronchiolitis obliterans organizing pneumonia (BOOP), was first described in the 1980s and is classified as a rare idiopathic interstitial pneumonia (IIP). COP classically presents in a subacute fashion following a flu-like illness with fever, non-productive cough, and fatigue. Imaging often reveals diffuse, bilateral, peribronchovascular and peripheral consolidative and ground glass opacities although various imaging subtypes also exist. Physical exam may be normal or reveal inspiratory crackles. Hypoxemia, when present, is commonly identified with exertion but can also occur at rest. Diagnostic evaluation relies on excluding secondary causes of organizing pneumonia and includes a thorough history including medications, exposures, and signs or symptoms of underlying rheumatologic disease. Invasive diagnostic testing including tissue sampling allows for histopathologic confirmation of COP while excluding secondary causes including infection and malignancy. While video-assisted thorascopic surgery (VATS) lung biopsy is often the preferred method of obtaining sufficient tissue, less invasive means may be employed based on patient-specific factors. A defining feature of COP is steroid-responsiveness, and most experts recommend prolonged corticosteroid courses (6-12 months). Response to corticosteroids and prognosis is typically excellent. Relapse rates range from 25-50% and occur most often during steroid taper or complete withdrawal necessitating additional therapy. Steroid-sparing immunosuppression may be used in select circumstances. Further study is needed to define optimal corticosteroid dose and duration.